TRANSFORMASI PENYIARAN DIGITAL: STUDI KASUS PENDIRIAN NUSANTARA TV SEBAGAI PELOPOR TELEVISI DIGITAL PERTAMA DI INDONESIA - Mellisa Marchelia (JURNAL ILMIAH NUSANTARA, 2026)
In the context of media disruption and the implementation of broadcasting migration policies from analog to digital systems, Nusantara TV emerged as a broadcasting institution that, since its inception, has fully implemented digital broadcasting. This study focuses on analyzing the strategies, stages, and contributions of Nusantara TV in accelerating the process of broadcasting digitalization in Indonesia. Using qualitative methods, research data was obtained through in-depth interviews with key informants directly involved in the dynamics of this digital transformation. The research findings indicate that Nusantara TV's transformation not only emphasizes technical aspects but also includes strategies for distributing set-top boxes, utilizing international-standard production and transmission technology, and logistics collaboration with third parties, such as PT Pos Indonesia, to expand broadcast reach to 3T areas (frontier, outer, and underdeveloped regions). Additionally, Nusantara TV actively supports digitalization regulation through the initiative to establish the Indonesian Digital Television Association (ATSDI). These research findings emphasize that the success of digital migration in the broadcasting industry is not solely determined by infrastructure readiness but is also influenced by the implementation of comprehensive strategies. (ATSDI). The findings of this study confirm that the success of digital migration in the broadcasting industry is not only determined by infrastructure readiness alone, but is also influenced by the implementation of comprehensive strategies, active involvement in national policies, and institutional innovation in facing the challenges of the media digitalization era.